Getting back into the swing of things: The adaptive path of purchasing and supply management in enhancing supply chain resilience. Issue 5 (December 2022) - Küffner, Christoph; Münch, Christopher; Hähner, Sven; Hartmann, Evi
Abstract: The COVID-19 crisis posed significant challenges to global supply chains (SCs) and exposed their vulnerability to disruption. As SCs have evolved into complex structures comprising a multitude of globally dispersed companies that collaborate closely with one another, purchasing and supply management (PSM) have played a key role in addressing the crisis. The existing PSM measures for increasing supply chain resilience (SCRES) were stress tested and it became evident that these methods are applicable only to a limited extent due to their static perspective and their lack of a network character. Thus, this paper examines the role of PSM by identifying implemented response measures. By conducting 40 semi-structured interviews with experts from original equipment manufacturers and first-tier suppliers in the German automotive industry, a comprehensive overview of the industry was obtained. To reflect the network nature of the industry and the adaptive path of PSM, the data analysis is framed by resource dependence theory and the adaptive cycle approach. The results of the study are 25 response measures of PSM to enhance SCRES, categorized into three waves of measures: initial measures upon the occurrence of the disruption, temporary measures during the disruption, and post-disruption measures. In this way, the study contributes to the existing literature by demonstrating that PSM takes on a major role in increasing resilience by implementing diverse response measures. In addition, the study shows that PSM follows the path of an adaptive cycle, and that after the disruption and the initial and temporary measures, PSM adapts, which is reflected in the post-disruption measures. For practitioners, the study provides a list of response measures to increase resilience that can be used to review existing measures or implement new ones. Highlights: Identifies and categorizes 25 response measures of PSM to cope with a disruption. Reveals three ' waves of measures ' for the implementation of response activities. Indicates the adaptive path of PSM as response to a disruption. Applies the resource dependence theory and adaptive cycle approach as theoretical underpinning. Conducts 40 interviews with representatives of PSM within the automotive industry.